Analisis Ayat – Ayat Ambiguity dalam Kajian Al – Isrsyad dan At - Tauriyah - Dini Febria Arifina; Mutia Zahara; Harun Alrasyid (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
In several disciplines of Arabic language learning, the science of balagha is one of the disciplines that is already familiar, which is then divided into three branches, namely: Ma'ani Science, badi' science and bayan science. Through badi' science, someone will be taught about the beauty of language both in terms of lafazh and meaning. This study was conducted to examine the division of badi' science from both. The research method used is a literature review (Search Library), the data of which is taken through a data collection method by understanding and studying theories from various literatures related to the research, for example books, journals and research that has been done. The results of the study show that the study of Badi' science from the perspective of the beauty of Meaning (Muhassinat Lafzhiyyah) is called Badi' At - Tauriyyah while the study of badi' science from the perspective of beauty through lafazh is called Badi' Al - Isrhad.